Neuronal synchronization in Drosophila - Florencia Fernandez-Chiappe; Marcos Wappner; Luis G. Morelli; Nara I. Muraro (iScience)
Summary: Collective rhythms are intrinsic to biological processes across temporal and spatial scales. In the brain, synchronized neuronal oscillations underlie collective rhythms essential for complex functions. Neuronal oscillations were reported in individual Drosophila neurons that underlie circadian and sleep behaviors. However, it is still unclear whether and how these participate in a collective rhythm. We perform whole-cell patch clamp recordings and demonstrate that membrane potential oscillations disappear after blocking nicotinic acetylcholine receptors. Perturbations to membrane potential do not change the phase of oscillation, further suggesting they depend on external inputs. We propose a theoretical description that accounts for experimental observations and predicts phase-locked neuronal synchronization. Simultaneous electrophysiological recordings of neuronal pairs confirm this prediction and show that this is a widespread phenomenon in accessory medulla neurons. Our findings suggest the possibility that brain waves may arise from collective neuronal activity within this region of the fly brain.